2021
DOI: 10.1002/smll.202007311
|View full text |Cite
|
Sign up to set email alerts
|

Hybridized Graphene for Supercapacitors: Beyond the Limitation of Pure Graphene

Abstract: Graphene‐based supercapacitors have been attracting growing attention due to the predicted intrinsic high surface area, high electron mobility, and many other excellent properties of pristine graphene. However, experimentally, the state‐of‐the‐art graphene electrodes face limitations such as low surface area, low electrical conductivity, and low capacitance, which greatly limit their electrochemical performances for supercapacitor applications. To tackle these issues, hybridizing graphene with other species (e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 170 publications
1
69
0
Order By: Relevance
“…To synthesize EGO, we used the apparatus and method as described comprehensively in our previous work. 19 The electrochemical glass tubular reactor is shown in Fig. 1a.…”
Section: Synthesis Of Ego and Regomentioning
confidence: 99%
See 1 more Smart Citation
“…To synthesize EGO, we used the apparatus and method as described comprehensively in our previous work. 19 The electrochemical glass tubular reactor is shown in Fig. 1a.…”
Section: Synthesis Of Ego and Regomentioning
confidence: 99%
“…14 With this motivation, a variety of graphene-derived materials, with a major focus on oxidation and elemental doping of graphene, 15,16 for high performance anodes of SIBs have been reported over the past decade. 14,[17][18][19] The oxidation of graphene can cause significant changes in electronic properties and reactivity with Na ion. [20][21][22] The role of oxygen functional groups for Na ion intercalation in graphene oxide (GO) has been studied using density functional theory (DFT), and it was found that epoxide groups attached on graphene oxide (GO) can make a great contribution to Na storage capacity as well as efficient charge transport.…”
Section: Introductionmentioning
confidence: 99%
“…Among carbon-based electrodes, although graphene has been considered one of the most promising electrode materials with remarkable conductivity and high theoretical surface area, the theoretical limit of the specific capacitance is 550 F g −1 . [5][6][7][8][9] Therefore, different strategies have been applied to improve the capacitance of carbon-based electrodes, among which a promising approach is to introduce pseudocapacitance by adding manganese oxides (MnO x ) due to their high theoretical capacitances and their earth-abundant and nontoxic nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, the zigzag network and overlarge pore size make the porous structures unsuitable for maximizing spatial charge storage. The onion-like, edge-oriented, or other particles with a large external surface and edge area can provide additional ion adsorption/desorption sites, enlarging the capacitance at the high-frequency region 7,18,[31][32][33] . Nevertheless, it always requires another scaffold to support these nanosized particles, leading to a critical influence on the high-frequency response.…”
Section: Introductionmentioning
confidence: 99%